Growth and Adjustment in East Asia and Latin America - José De Gregorio; Jong-wha Lee (Asian Development Bank Institute (ADBI), 2004)
This paper compares the experience of growth performance and macroeconomic adjustment between East Asia and Latin America from 1970 to 2000. We find that the difference in growth performance between the two regions can be largely attributed to the differences in fundamental growth factors such as investment rate, human resources, fertility, institutional quality, macroeconomic stability and degree of trade openness. We also discuss the role of the quality of education and differences in inequality. Balance-of-payments crisis shocks have also contributed significantly to differences in growth performance. Our analysis reveals that growth rates tend to fall only temporarily following balance-of payments crises and then rebound to the pre-crisis levels, producing the typical v-type pattern for output in both East Asia and Latin America. However, a balance-of-payments crisis is often associated with a large decline of growth rates and develops into another crisis. Analyzing the determinants of the output cost of crises, we find that international liquidity, financial soundness, real exchange rate depreciation and monetary policy play a critical role in reducing output losses.
hdl:11540/4159
Keywords: 330; Wirtschaftswachstum; Wirtschaftliche Anpassung; Lateinamerika; Ostasien